2006
DOI: 10.1111/j.1471-1842.2006.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

The costs and effectiveness of information‐skills training and mediated searching: quantitative results from the EMPIRIC project

Abstract: Objectives : To compare the effectiveness and costs of providing information for patient care via librarian-mediated searches and information-skills training. Methods : A questionnaire survey to library staff and health professionals in the North West. Data was collected on perceptions of services, satisfaction and service usage, allowing a cost analysis to be undertaken. Statistical data was analysed using Statistical Package for the Social Sciences (  ). Results : Using satisfaction and use of skills as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
2
16
1
Order By: Relevance
“…This finding is similar to a previous study by Ely et al, who reported that physicians did not seek answers to many of their questions (55%), often suspecting a lack of usable information [16]. A recent study compared the effectiveness and costs of providing information for patient care via librarian-mediated searching versus information skills training for health professionals and found that both were similar [17]. Our results also suggest that it is less costly for librarians to locate relevant information than primary care providers.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is similar to a previous study by Ely et al, who reported that physicians did not seek answers to many of their questions (55%), often suspecting a lack of usable information [16]. A recent study compared the effectiveness and costs of providing information for patient care via librarian-mediated searching versus information skills training for health professionals and found that both were similar [17]. Our results also suggest that it is less costly for librarians to locate relevant information than primary care providers.…”
Section: Discussionsupporting
confidence: 86%
“…Either training is less successful for this group of people, or there is a 'confidence gap' when putting the skills they have found in practice, as has been noted elsewhere. 22 The majority of health professionals (almost two-thirds) believed their skills improved and were satisfied with the results of their searches reported in the previous paper, 4 indicating that training was effective. Nevertheless, this leaves a large proportion for whom training could be seen as unsuccessful and a closer examination of the findings showed that one-third believed that training was unsuccessful in formulating search questions, improving search skills or reducing the time taken to find information.…”
Section: Discussionmentioning
confidence: 80%
“…3 The quantitative data is reported in the first paper, in a previous issue of Health Information and Libraries Journal. 4 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health Libraries Australia has no expert searching guidelines, specialised qualification or registration in expert searching, or a requirement for members to maintain CPD. The literature search revealed no uniform guidelines or ‘…standard and validated methods of assessing the quality of mediated searches…’ 75 by librarian organisations. Without such quality control for mediated searches, what issues have been reported in the literature?…”
Section: Discussionmentioning
confidence: 99%